New leak element based on transfer-free single-layer graphene membrane. (January 2022) - Wang, Xudi; Lin, Hanwen; Bi, Hailin; Cao, Qing; Meng, Donghui; Sun, Lichen; Ren, Guohua; Qi, Jiadong; Zhang, Jun
Abstract: In this work, a new leak element based on transfer-free single-layer graphene was developed. The single-layer graphene was synthesized on Cu foil and small holes of about 10 μm were drilled on Cu foil to reveal graphene membrane. The conductance of He, N2 and Ar through the graphene leak element was measured based on the difference method. The results imply that various gases exhibit molecular flow regime under pressures ranging from vacuum up to 10 5 Pa, and the conductance of the transfer-free graphene is about two orders of magnitude smaller than that of the wet-transferred graphene. The difference of conductance may result from the generation of micron-sized cracks and tears on graphene surface during wet-transfer process. The transfer-free single-layer graphene developed in this work is an excellent material for low-permeation leak element. Highlights: A new leak element is developed based on transfer-free single-layer graphene membrane. The photolithography process is applied to drill small holes of about 10 μm on Cu foil to reveal graphene membrane. To eliminate the influence of sealing material, VCR all-metal sealing joints are used to form the leak elements. The gas flow through graphene is in molecular flow regime at pressure up to 10 5 Pa. The conductance of transfer-free graphene is about two orders of magnitude smaller than wet-transferred graphene.